Circular trajectory weaving welding control algorithm based on space transformation principle. (October 2019) - Kang, Cunfeng; Liu, Zixiao; Chen, Shujun; Jiang, Xiaoqing
Abstract: This paper developed a novel circular trajectory weaving welding control algorithm based on the space transformation principle. The three-dimensional weaving control problem was simplified into two-dimensional by establishing a basic plane. First, the transformation matrix between the basic plane and the weaving plane was solved by using the teaching parameters. The basic weaving point in the basic plane was obtained by using multiple weaving parameters. The basic weaving point was mapped to the weaving plane by the transformation matrix to obtain the final trajectory for the weaving welding. The above algorithm in combination with Ferguson Smooth algorithm was used as a novel control strategy which can effectively solve the problem of velocity discontinuity at sharp corners. The simulation and welding experiment results showed that this strategy can process more input weaving parameters and generate a more accurate circular trajectory. Therefore, this weaving welding control algorithm has a high practical value.